Psychosocial conflicts and defense mechanisms in leadership: psychoanalytic view in Elizabeth: The Golden Age movie - Al Fajri, Al Syifa An Nisaa; Kusuma, Agung Wiranata (Universitas Mulawarman, 2025)
This study examines the personality structure of the character Elizabeth, who is the Queen of England in the film Elizabeth: The Golden Age (2007) through the theory of Sigmund Freud, as well as the psychosocial development of Erik Erikson's theory, and the defense mechanisms of Sigmund Freud's theory that she uses. This study uses a qualitative descriptive method with content analysis, examining the elements of dialogue and character behavior in the film. Data for this study were collected by watching the film, noting relevant scenes, and analyzing them according to the theory used. The results of the study show that Elizabeth experiences internal conflict between her id, ego, and superego and this reflects how she develops as a national leader. Erikson's psychosocial stages such as Identity vs Role Confusion, Intimacy vs Isolation, and Generativity vs Stagnation, show Elizabeth's changes when dealing with matters related to politics and society. In addition, the defense mechanisms used by Elizabeth such as rationalization and sublimation play a positive role in maintaining her emotional stability, while regression and forgiveness lead to negative ones.